Technology hypes: Practices, approaches and assessments - Bareis, Jascha; Roßmann, Maximilian; Bordignon, Frédérique (TATuP - Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis, 2023)
To date, the study of hype has become a productive but also eclectic field of research. This introduction provides an overview of the core characteristics of technology hype and distinguishes it from other future-oriented concepts. Further, the authors present promising approaches from various disciplines for studying, critiquing, and dealing with hype. The special issue assembles case studies, methodological and theoretical contributions that analyze tech hypes’ temporality, agency, and institutional dynamics. It provides insights into how hypes are triggered and fostered, but also how they can be deconstructed and anticipated.